Zu Walter Benjamins "Denkbildern“ - König, Peter (Odradek, 2016)
The term „Denkbild“ is nowadays commonly used to characterize a certain genre of Benjamin’s literary production, associated with the Einbahnstraße and the Berliner Kindheit um neunzehnhundert, although Benjamin himself never used this concept. After giving a criticial account of how this came to be the paper argues that there might have been reasons why Benjamin could have thought that the expression “Denkbild” was not fully adequate to describe his intentions in regard to the prose texts subsumed under this title. Focusing on the concept of “image” which is ubiquitous in Benjamin’s writing the paper shows that an image according to Benjamin always comprehends a tension between opposite determinations, i.e. between life and lifelessness, being and illusoriness, proximity and distance, trace and aura. All these oppositions can be traced back to the ultimate opposition between a symbolic and an allegoric spirit of language. Since Benjamin’s “Denkbilder” seem intended to appeal to the symbolic spirit of language the paper suggests that after all it might be more fitting and for further critical appraisal more fruitful to speak instead of “Sinnbilder”.
Gesehen am 03.12.2020